Ekuitas Merek Platform Berbasis Teknologi di Instagram - Raden Muhammad Jihad Muharram; Anne Ratnasari (Bandung Conference Series: Communication Management, 2023)
Abstract. The title of this research is “TECHNOLOGY BASED PLATFORM BRAND EQUITY ON INSTAGRAM (Case Study on Instagram @readylearn social media)” The rapid development of the times is increasingly refining technology on the Internet. Especially in education, where technology-based platforms are already in use, technology can complete a variety of disciplines. Various kinds of platform brands have been born in the field of education to help the knowledge of Indonesian people. Therefore, researchers are interested in conducting a survey on ReadyLearn through a survey called "Brand Equity, a Technology-Based Learning Platform on Instagram (Instagram @readylearn Case Study on Social Media)." This study uses a qualitative approach with a case study approach. The survey method was conducted using interviews, documentation, and literature searches. In this study, the informants who became the resource persons were people who had credibility and ability in the field of education. The purpose of this research is to provide Readylearn learning materials, implement all aspects of the online tutor startup business scope that focuses on education, especially general products and features and can be used as a reference on the characteristics of the target market. Abstrak. Penelitian ini berjudul EKUITAS MEREK PLATFORM BERBASIS TEKNOLOGI DI INSTAGRAM (Studi Kasus Pada Media Sosial Instagram @readylearn) Perkembangan jaman yang pesat membuat teknologi semakin canggih dengan adanya internet. Berbagai bidang dapat disempurnakan dengan teknologi, terkhusus dalam bidang Pendidikan yang sudah menggunakan platform berbasis teknologi. Berbagai macam merek platform yang lahir di dalam bidang Pendidikan untuk membantu masyarakat Indonesia dalam hal ilmu pengetahuan. Maka dari itu, peneliti tertarik untuk melakukan penelitian kepada ReadyLearn melalui penelitian “Ekuitas Merek Platform Belajar Berbasis Teknologi di Instagram (Studi Kasus pada Media Sosial Instagram @readylearn)”. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Metode penelitian dilakukan dengan menggunakan wawancara, dokumentasi, dan penelusuran literatur. Dalam penelitian ini, informan yang menjadi narasumber adalah orang yang mempunyai kredebilitas dan kemampuan di bidang pendidikan. Tujuan penelitian ini adalah memberikan materi pembelajaran Readylearn, mengimplementasikan semua aspek lingkup bisnis startup tutor online yang fokus pada bidang pendidikan, terutama produk dan fitur umum serta dapat digunakan sebagai referensi pada karakteristik pasar sebagai sasarannya.